INFLUENCE OF LEADERSHIP STYLE, MOTIVATION AND DISCIPLINE TO WORK PRODUCTIVITY OF DEPARTMENT MARINE AND FISHERIES - Bachtiar Dwi Prasetyo; Harsuko Riniwati (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2016)
The research done on Department Marine and Fisheries in Situbondo, East Java on February 2016. The research aim to investigate and analyze the influence of: (1) leadership style, job motivation, work discipline and work productivity of employee in Department Marine And Fisheries Situbondo, (2) the influence of leadership style, job motivation, and work  discipline of work productivity on employee in Department Marine And Fisheries Situbondo, (3) the influence of dominant variable of work productivity on employee in Department Marine And Fisheries Situbondo.The method used in this research: type of research is descriptive, the type of data in this research is quantitative and qualitative data, data sources are primary data and secondary data, sampling technique using techniques saturated, data collection techniques use observation, interviews, questionnaires and documentation, instrument measurement techniques using a likert scale, and analysis of data using multiple regression analysis. The results showed leadership style variables did not significantly affect of work productivity since it has significant value or an error rate of 0.986, or 98.6%, while job motivation variable and work discipline have real impact on work productivity with their respective significant value or an error rate of 0.005 or 0.5% and 0,105 or 10.5%. Key word:  leadership style, job motivation, work discipline, work productivity